IMPLEMENTASI KONSELING INDIVIDU DENGAN TEKNIK SELF MONITORING UNTUK MENGURANGI KECANDUAN GAME ONLINE SISWA SMK ABDUL AZIZ CURAHLELE BALUNG JEMBER - Imam Hambali; Imaratul Uluwiyah; Ika Romika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
One phenomenon of students who frequently play online games is students at SMK Abdul Aziz Curahlele Balung Jember. Then this is what prompted researchers to provide solutions and guidance to students who frequently play online games. This guidance uses self-monitoring techniques which are then developed by researchers into research. Self-monitoring guidance techniques are simply defined as guidance therapy for solving someone's problems with mastery from within themselves. The research written by this researcher has 2 objectives: general objective and specific objective. The general objective on this research is to complete the researcher's final assignment as a final year student. The specific objective is to overcome the problem of students frequently playing online games at SMK Abdul Aziz Curahlele Balung Jember so that students can return to focusing on studying at school. This research use a qualitative approach with case study research design that aims to determine the effect of individual counseling using self-monitoring techniques to reduce online game addiction. The results of this research are to resolve and alleviate the problem of students at SMK Abdul Aziz Curahlele Balung Jember frequently playing online games so that they do not focus on learning. In addition, this research can be imitated and reviewed by various groups in its application.